APATHETIC HYPERTHYROIDISM: WHEN A COMMON DIAGNOSIS COMES WITH UNCOMMON MANIFESTATIONS - Wong, Wei Ton; Chong, Jia Chuan; Daud, Puteri Wan Seribani Mat (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND The classic symptoms of hyperthyroidism include heat intolerance, tremors, palpitations, anxiety, weight loss despite an increased appetite, diarrhea, and breathlessness. In this case report, we looked at a case of atypical presentation of hyperthyroidism. CASE A 66-year-old-male with underlying diabetes mellitus, hypertension, chronic kidney disease and gout presented with 1 week history of fever, lethargy, reduced appetite and giddiness. Unintentional weight loss was noted. Vital signs were stable with no tachycardia. Thyroid eye signs, tremor, and goiter were absent. ECG showed sinus rhythm. Initial lab data were significant for ALT 78 U/L, AST 68 U/L and ALP 140 U/L. He was started on empiric antibiotics and was worked up for the presence of a possible malignancy. Total bilirubin, hepatitis screening and tumor markers (CEA, Ca 19-9, PSA, AFP) were unremarkable. Subsequent blood tests showed worsening ALT 150 U/L, AST 133 U/L and ALP 156. Abdominal ultrasound revealed no signs of intra-abdominal fluid collection. After a week of antibiotics, the patient continued to complain of lethargy. Hence, more investigations were conducted. Surprisingly, the results showed TSH <0.005 mIU/L and T4 >78.10 pmol/L, indicative of the diagnosis of apathetic hyperthyroidism. The patient was started on Lugol’s iodine 10 drops TDS for 10 days, T. cholestyramine 4 g TDS and discharged with the plan to start thionamides once his liver function improves. CONCLUSION Apathetic hyperthyroidism is a rare presentation of thyrotoxicosis. It poses diagnostic challenges due to the lack of characteristic signs and symptoms associated with hyperthyroidism. This can be attributed to decreased adrenergic tone, changes in the autonomic nervous system, and tissue resistance to thyroid hormone effects at the cellular level. Apathetic hyperthyroidism should be suspected in an elderly patient exhibiting inexplicable lethargy, weight loss, and depression.